Association between human herpesvirus 6 status and sarcopenia risk: a UK biobank cohort study with sex-specific patterns and telomere length modification - Liu, Xiangliang; Yang, Wang; Chen, Xinqiao; Liu, Yuting; Zhao, Yixin; Li, Yuguang; Chen, Naifei; Cui, Jiuwei (Frontiers in Immunology, 2025)
BackgroundSarcopenia represents a significant global health concern affecting older adults, yet its relationship with infectious agents remains poorly understood. This study investigated the association between human herpesvirus 6 (HHV-6) status and sarcopenia risk, examining potential sex-specific differences and biological modifiers.MethodsWe analyzed data from 339,085 UK Biobank participants for baseline assessment and 27,030 participants for follow-up analysis. HHV-6 status was determined using TaqMan qPCR assay targeting conserved viral regions (DR1 and U7). Sarcopenia was defined according to European Working Group on Sarcopenia in Older People 2 (EWGSOP2) criteria. Multivariable logistic and Cox proportional hazards regression models were employed to assess associations, adjusting for comprehensive demographic, behavioral, and clinical covariates.ResultsIndividuals with DR-only positive HHV-6 status exhibited significantly elevated odds of sarcopenia at baseline (OR = 3.77, 95% CI: 1.44-8.08) and approximately fivefold increased risk during follow-up (HR = 4.76, 95% CI: 1.19-19.10). Sex-stratified analyses revealed pronounced male vulnerability to DR-only positivity (OR = 5.23, 95% CI: 1.74-12.60), while females showed associations only with typical positive status (OR = 1.63, 95% CI: 1.00-2.49). Telomere length significantly modified these relationships, with stronger associations among males with longer telomeres (OR = 6.57, 95% CI: 1.43-30.16) and females with shorter telomeres (OR = 1.94, 95% CI: 1.08-3.49). Results remained consistent across sensitivity analyses using alternative sarcopenia definitions.ConclusionsThis study identifies novel associations between HHV-6 status, particularly DR-only positivity, and increased sarcopenia risk in a sex-specific manner. These associations are further modified by telomere length, indicating potential interactions between viral integration, cellular senescence, and muscle health. Our findings contribute to emerging research on infectious correlates of age-related muscle deterioration and may inform future investigations into preventive strategies.